Transcriptional Pattern Analysis of Virus-Specific CD8+ T Cells in Hepatitis C Infection: Increased Expression of TOX and Eomesodermin During and After Persistent Antigen Recognition - Wildner, Nils H.; Walker, Andreas; Brauneck, Franziska; Ditt, Vanessa; Peine, Sven; Huber, Samuel; Haag, Friedrich; Beisel, Claudia; Timm, Joerg; Schulze zur Wiesch, Julian (Frontiers in Immunology, 2022)
Thymocyte Selection-Associated High Mobility Group Box (TOX) has been described to be a key regulator in the formation of CD8+ T cell exhaustion. Hepatitis C virus (HCV) infection with different lengths of antigen exposure in acute, chronic, and after resolution of HCV infection, is the ideal immunological model to study the expression of TOX in HCV-specific CD8+ T cells with different exposure to antigen. HCV-specific CD8+ T cells from 35 HLA-A*01:01, HLA-A*02:01, and HLA-A*24:02 positive patients were analyzed with a 16-color FACS-panel evaluating the surface expression of lineage markers (CD3, CD8), ectoenzymes (CD39, CD73), markers of differentiation (CD45RO, CCR7, CD127), and markers of exhaustion and activation (TIGIT, PD-1, KLRG1, CD226) and transcription factors (TOX, Eomesodermin, T-bet). Here, we defined on-target T cells as T cells against epitopes without escape mutations and off-target T cells as those against a "historical" antigen mutated in the autologous sequence. TOX+HCV-specific CD8+ T cells from patients with chronic HCV and on-target T cells displayed co-expression of Eomesodermin and were associated with the formation of terminal exhausted CD127-PD1hi, CD39hi, CD73low CD8+ T cells. In contrast, TOX+HCV-specific CD8+ T cells in patients with off-target T cells represented a progenitor memory Tex phenotype characterized by CD127hi expression and a CD39low and CD73hi phenotype. TOX+HCV-specified CD8+ T cells in patients with a sustained virologic response were characterized by a memory phenotype (CD127+, CD73hi) and co-expression of immune checkpoints and Eomesodermin. Indicating a key structure in priming of HCV-specific CD8+ T cells in the chronic stage, which persisted as a residual after therapy. Overall, the occurrence of TOX+HCV-specific CD8+ T cells was revealed at each disease stage, which impacted the development of progenitor Tex, intermediate Tex, and terminally exhausted T cell through an individual molecular footprint. In sum, TOX is induced early during acute infection but is modulated by changes in viral sequence and antigen recognition. In the case of antigen persistence, the interaction with Eomesodermin leads to the formation of terminally exhausted virus-specific CD8+ T cells, and there was a direct correlation of the co-expression of TOX and Eomes and terminally exhausted phenotype of virus-specific CD8+ T cells.